Analysis of Factors Affecting The Incidence of Leptospirosis in Semarang City in 2024 - Wiwik Dwi Lestari; Titi Indriyati; Ajeng Tyas Endarti (International Journal Labs, 2025)
Background: Leptospirosis is a zoonotic infectious disease caused by Leptospira bacteria and remains a significant public health problem in tropical regions. Semarang City is one of the areas with a high risk of leptospirosis due to its geographical structure, frequent flooding, poor sanitation, and high population density. Data from the Semarang City Health Office in 2024 reported 32 cases and 5 deaths, with cases increasing during the rainy season. Several determinants, including behavioral, environmental, socioeconomic, and demographic factors, contribute to disease transmission. Objective: This study aims to identify the factors influencing the incidence of leptospirosis in Semarang City in 2024. Methods: A quantitative case-control study was conducted involving 96 respondents residing in Semarang City, consisting of 32 cases and 64 controls. Data were analyzed using univariate, bivariate, and multivariate logistic regression. Results: Bivariate analysis showed that gender (p=0.000; OR=51.13), the presence of rats (p=0.000; OR=0.094), the presence of livestock (p=0.002; OR=4.26), and the presence of garbage (p=0.000; OR=11.88) were significantly associated with leptospirosis incidence. However, age (p=0.393; OR=1.426) and education level (p=0.516; OR=0.684) were not significantly related. Multivariate analysis confirmed that gender (p=0.000; OR=287.491; CI=19.611–421.478), livestock (p=0.003; OR=60.152; CI=4.089–884.845), and garbage around the house (p=0.002; OR=52.681; CI=4.794–578.888) were influential factors. Gender was identified as the dominant factor, increasing the risk up to 287.491 times. Recommendation: Strengthened multisectoral collaboration between government agencies, communities, and healthcare workers is essential to enhance environmental sanitation, rodent control, and surveillance to prevent leptospirosis in Semarang City.